Acute kidney injury following COVID-19 and risk factors for progression to chronic kidney disease (Annals of Medical Research, 2022)
Aim: Acute kidney injury (AKI) is one of the frequent complications of COVID-19 infection. The predictors of progressive kidney disease for patients with COVID-19- associated AKI (COV-AKI) are unclear. In our study, we aimed to demonstrate the risk factors of non-recovery of COV-AKI.Materials and Methods: COV-AKI developed in 901 of 3,337 patients treated in our hospital for COVID-19 between April 1, 2020 and November 30, 2020. 331 of 901 patients with COV-AKI died at the hospital. Of these patients, 459 patients who met the inclusion criteria were included in the study, while 111 patients were excluded. At 3 months post-AKI, 399 of 459 cases (Group 1) recovered from AKI, and 60 (Group 2) did not.Results: The median age of the patients included in the study was 68 (59-76), and 44.9% (206) of them were women. Thirty-five of 60 patients in Group 2 developed de novo chronic kidney disease while 25 patients had a history of chronic kidney disease (CKD) and experienced a disease progression. We found that patients with low serum albumin levels (hypoalbuminemia) at  admission (P
Keywords: Acute kidney injury; COVID-19; Hypoalbuminemia